(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The paper presents the first data on slug mites Riccardoella (Riccardoella) limacum (Schrank) and R. (Proriccardoella) oudemansi Thor (Acari: Ereynetidae) in Serbia. The two parasitic species were detected on seven species of snails and slugs (Gastropoda, Pulmonata) in Serbia. Riccardoella limacum, which is a specialized snail parasite, was found in Helix pomatia L. and H. lucorum L species of the family Helicidae. Riccardoella oudemansi was found exclusively on slug species: Arion lusitanicus Mabille (Arionidae), Tandonia budapestensis (Hazay) (Milacidae), Limacus flavus (L.), Limax maximus L. and L. cinereoniger Wolf (Limacidae).